Performance and Carcass Characteristics of Broiler Chickens Fed Various Components of Candlenut Kernel - Rasid, R. A.; Baba, A. R.; Yaakub, N. M.; Milan, A. R. (Tropical Animal Science Journal, 2019)
One-hundred male broiler chickens (Cobb500) were assigned randomly in a completely randomized design (CRD) into four dietary treatment groups to determine the effects of various components (whole kernel, kernel oil, kernel defatted) of candlenut (Aleurites moluccana) kernel on growth performance, carcass yield, and proximate and fatty acid composition in meat during the grower-finisher stage. Each treatment consisted of 5 replicates with 5 birds for each replications. From 21 to 42 days of age, the birds were offered either one of the following dietary treatments namely; Basal diet containing no candlenut kernel (T1), Basal diet containing 2.5% whole candlenut kernel (T2), Basal diet containing 2.5% candlenut kernel oil (T3), and Basal diet containing 2.5% candlenut kernel defatted (T4). The significant difference was determined when the probability level was p<0.05. Birds fed the experimental diets showed no significant difference on growth performance, carcass yield, and proximate and fatty acid compositions in meat. However, birds fed diets containing various components of candlenut had small effect on reducing feed intake, decreasing crude protein and crude fat contents in meat, and increasing total C18:2n-6 and n-6 PUFA. In conclusion, supplementation of various components of candlenut kernel in broiler diet did not improve growth performance, carcass yield, and proximate and fatty acid compositions in meat.